2017
DOI: 10.11622/smedj.2016126
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of critical incidents in the post-anaesthesia care unit at a major tertiary hospital

Abstract: INTRODUCTIONWe reviewed patients with critical incidents that occurred in the post-anaesthesia care unit (PACU) at a major tertiary hospital, and assessed the effect of these incidents on PACU length of stay and discharge disposition.METHODS A retrospective review was conducted of patients in the PACU over a two-year period from 24 June 2011 to 23 August 2013. Data on critical incidents was recorded in the administrative database using a standardised data form. RESULTSThere were 701 incidents involving 364 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 14 publications
(18 reference statements)
1
25
1
2
Order By: Relevance
“…The length of stay in PACU greater than 4 hours (AOR=4.538;95% CI (2.089 -9.857) were strongly correlated with the incidence of PACU complication, our study also observed that patients who encountered PACU complications signi cantly required a prolonged duration of stay than initially planned compared to patients without complications (9,22).…”
Section: Discussionsupporting
confidence: 66%
“…The length of stay in PACU greater than 4 hours (AOR=4.538;95% CI (2.089 -9.857) were strongly correlated with the incidence of PACU complication, our study also observed that patients who encountered PACU complications signi cantly required a prolonged duration of stay than initially planned compared to patients without complications (9,22).…”
Section: Discussionsupporting
confidence: 66%
“…An institution-based prospective follow up study was conducted from April 20, 2021 to June 28, 2021 to determine the incidence and predictive factors of hemodynamic instability in the post anesthesia care unit of a comprehensive specialized referral hospital in Ethiopia. This paper was registered in research registry with unique identifying number [ 23 ] of 7543 and was guided by STROCSS 2021 checklist [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although this preoccupation with failure is a key principle of HRO, it is often ignored in healthcare [ 8 ]. Retrospective reviews and incident reports have highlighted how healthcare staff often assumes that what is in front of them is correct and do not approach tasks with a mindset to look for potential errors [ 9–12 ].…”
Section: Introductionmentioning
confidence: 99%